Data manipulation in Python (Manning Publications, 2022)
Data science is fast becoming one of the most well-suited occupations for success in the twenty-first century, and the need for data scientists has been increasing in the employment market over the last several years. The work is computerized, programming-driven, and analytical in nature, a natural fit for people with a unique mix of scientific training, computer expertise, and analytical abilities. If you have an interest in data science, this course will provide you with the skills and knowledge you need to enter this career path. Learn to work with data in Python—the language most often used in data analysis—on the Jupyter Notebook platform. Install and explore essential Python libraries for data science. Use the NumPy library to apply numerical operations to data. Work with data structures in Pandas, a powerful open-source tool built on top of NumPy. There’s a lot to learn, so this course goes step-by-step, skill-by-skill, and exercise-by-exercise. Each lesson builds on previous lessons to reinforce and build on what you’ve learned. Our goal is to equip you with all the tools you need to learn, practice, and master Python, Numpy & Pandas. You'll walk away from each video with a fresh idea that you can put to use right away!